Europium-doped NaYF4 nanoparticles cause the necrosis of primary mouse bone marrow stromal cells through lysosome damage. Issue 26 (23rd February 2016) - Ge, Kun; Sun, Wentong; Zhang, Shaohan; Wang, Shuxian; Jia, Guang; Zhang, Cuimiao; Zhang, Jinchao
Abstract : Applications of europium-doped NaYF4 (NaYF4 :Eu 3+ ) nanoparticles in biomedical fields will inevitably increase their exposure to humans, therefore, the assessment of toxicities must be taken into consideration. Abstract : Applications of europium-doped NaYF4 (NaYF4 :Eu 3+ ) nanoparticles in biomedical fields will inevitably increase their exposure to humans, therefore, the assessment of toxicities must be taken into consideration. It was reported that NaYF4 :Eu 3+ nanoparticles could accumulate in the bone. However, the potential effect of NaYF4 :Eu 3+ nanoparticles on bone marrow stromal cells (BMSCs) has not been reported. In this study, NaYF4 :Eu 3+ particles with diameters of 50 and 200 nm (NY50 and NY200) were prepared and characterized by scanning electron microscopy, transmission electron microscopy, powder X-ray diffraction, photoluminescence excitation and emission spectra, and dynamic light scattering. The cytotoxicity of NaYF4 :Eu 3+ particles on BMSCs and the associated mechanisms were further studied. The results indicated that NaYF4 :Eu 3+ particles could be uptaken into BMSCs and primarily localized in the lysosome. NaYF4 :Eu 3+ particles effectively inhibited the viability of BMSCs in a size-dependent manner at 24 and 48 h. After cells were treated with 20 μg mL −1 of NY50 and NY200 for 24 h, NaYF4 :Eu 3+ particles could trigger cell necrosis in a size-dependent manner. The percentage of necrotic BMSCs (PI + /Annexin V − ) increased to 15.93 and 14.73%. Necrosis was further verified by increased lactate dehydrogenase leakage. Meanwhile, both NY50 and NY200 induced an increased cell population in the S and G2/M phases. The following mechanism is involved in NaYF4 :Eu 3+ particle-induced BMSCs necrosis: the NaYF4 :Eu 3+ particles lead to lysosomal rupture by lysosomal swelling, permeabilization of lysosomal membranes, and increased cathepsins B and D. In addition, NaYF4 :Eu 3+ particle-induced BMSCs necrosis is also directly caused by the overproduction of ROS through injury to the mitochondria. This study provides novel evidence to elucidate the toxicity mechanisms for bone metabolism and may be beneficial to more rational applications of these nanomaterials in the future.